Governance mechanism and risk management of Congolese commercial banks - Louison TETE SULA; Yannick NSIESILA MANZANZA; Alain PAYANZO NTSOMO (Academic Finance)
Purpose : This study evaluates the impact of accounting governance and quality management on the risks of commercial banks in the Democratic Republic of Congo.